The changes in microstructural features and physical properties of ceramic matrix composite bonding tools under ultrasonic service - THEERAPAPVISETPONG, Apirat; SERIVALSATIT, Karn; REAINTHIPPAYASAKUL, Wuttichai; BUGGAKUPTA, Wantanee (Journal of Metals, Materials and Minerals, 2023)
Tape automated bonding (TAB) process plays a key role in the production of disk drives, microchips and other microelectronics components. Such tools should sustain their structures and properties throughout ultrasonic operation and are expected to last until reaching the targeted numbers of TAB cycles. This project aims to evaluate the changes in microstructures and physical properties of the bonding tools under ultrasonic service. Three commercial waffle-type tools from different suppliers were focused, namely Tool A, Tool B and Tool C. They provide different levels of bonding efficiency up to 50k cycles under relatively similar ultrasonic practice. Non-destructive and destructive testing methods were examined by the means of X-Ray and mass spectroscopy techniques, respectively. The waffle-end tips of the selected tool were observed using a confocal microscope. The changes in grain size and grain size distribution before and after ultrasonic service were quantitatively analyzed via electron micrographs. Also, their bulk density, hardness and toughness were determined. The experimental work revealed the variation in microstructural features and properties among the three, leading to the difference in ultrasonic efficiency, even they all contained similar phase composition. The relationship between microstructures, properties and ultrasonic efficiency was also reported and discussed.